Comparison of the impact of continuous and intermittent exposure to vinyl chloride, including phenobarbital effect - Jedrychowski, R A; Sokal, J A; Chmielnicka, J (Journal of hygiene, epidemiology, microbiology, and immunology, 1985)
Rats were subjected to 4 h continuous and intermittent exposure to vinyl chloride (VC) at the time-weighted average concentration of 50,000 mg/m3. Prior to exposure, half of the animals obtained water, whereas the other half 0.1% sodium phenobarbital (PB) solution for seven consecutive days. The studies were focussed on: body weight, liver weight, activity of enzymes in the blood serum, activity of glutathione S-transferase in the liver cytoplasmatic and microsomal fraction, content of free non-protein sulfhydryl groups (NPSH) in the liver and urinary excretion of thiodiglycolic acid (TDGA). VC exposure, both continuous and intermittent, resulted in a decrease of body weight, NPSH depletion in the liver and TDGA urinary excretion. PB effects were manifested by the persistent decrease in rats' body weight, increase in the liver weight, increase in the cytoplasmatic activity of glutathione S-transferase in the liver and increase in TDGA urinary excretion. With none of the tested parameters, except TDGA, statistically significant differences between the continuous and intermittent VC exposure at the same time-weighted average concentration of 50,000 mg/m3, were found. TDGA urinary excretion was higher in rats poisoned in continuous exposure, as compared to the intermittent one.
Keywords: Liver; Microsomes, Liver; Rats; játra; Thioglycolates; alkalická fosfatasa; vystavení vlivu životního prostředí; vinylové sloučeniny; vinylchlorid; L-Iditol 2-Dehydrogenase; Vinyl Compounds; Time Factors; alanintransaminasa; sorbitoldehydrogenasa; Vinyl Chloride; glutathiontransferasa; mužské pohlaví; L-laktátdehydrogenasa; Environmental Exposure; Alanine Transaminase; Alkaline Phosphatase; krysa rodu Rattus; Body Weight; Glutathione Transferase; Organ Size; velikost orgánu; aspartátaminotransferasy; thioglykoláty; zvířata; Aspartate Aminotransferases; L-Lactate Dehydrogenase; tělesná hmotnost; časové faktory; jaterní mikrozomy; fenobarbital; Phenobarbital; Male; Animals